1998
DOI: 10.1016/s0896-6273(00)80519-x
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in AP-3 δ in the mocha Mouse Links Endosomal Transport to Storage Deficiency in Platelets, Melanosomes, and Synaptic Vesicles

Abstract: The mouse mutant mocha, a model for the Hermansky-Pudlak storage pool deficiency syndrome, is characterized by defective platelets, coat and eye color dilution, lysosomal abnormalities, inner ear degeneration, and neurological deficits. Here, we show that mocha is a null allele of the delta subunit of the adaptor-like protein complex AP-3, which is associated with coated vesicles budding from the trans-Golgi network, and that AP-3 is missing in mocha tissues. In mocha brain, the ZnT-3 transporter is reduced, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
408
2
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 381 publications
(434 citation statements)
references
References 52 publications
16
408
2
5
Order By: Relevance
“…29 AP3 is a heterotetrameric adaptor protein involved in the biogenesis of lysosome-related organelles, such as platelet-dense bodies. The 'mocha' mouse mutant with a null allele of Ap3d1 shows bleeding abnormalities due to the storage pool deficiency in the dense granules of platelets, 30 raising the possibility that AP3D1 functions as the modulator of thrombogenesis via platelet function.…”
Section: Discussionmentioning
confidence: 99%
“…29 AP3 is a heterotetrameric adaptor protein involved in the biogenesis of lysosome-related organelles, such as platelet-dense bodies. The 'mocha' mouse mutant with a null allele of Ap3d1 shows bleeding abnormalities due to the storage pool deficiency in the dense granules of platelets, 30 raising the possibility that AP3D1 functions as the modulator of thrombogenesis via platelet function.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have demonstrated that SVs can be budded from the endosomal compartment with the use of AP-3 and the small GTPase ADP ribosylation factor 1 (Faundez et al, 1997 as well as being brefeldin A-sensitive (Shi et al, 1998). However, AP-3 ␦ subunit mutants in mouse are viable and contain an abundance of normal SVs, suggesting this is not an obligate pathway (Kantheti et al, 1998). In addition, recent data have documented that a third route of SLMV formation, from the late endosome, also exists in PC12 cells.…”
Section: Synaptic Localization Signals In Other Systemsmentioning
confidence: 99%
“…Recently, another ubiquitously expressed adaptor-related complex, AP-3, was described (Simpson et al, 1996(Simpson et al, , 1997Dell'Angelica et al, 1997) and shown to be involved in the delivery of proteins to lysosomes and lysosome-related organelles, including the yeast vacuole (Cowles et al, 1997;Panek et al, 1997) and insect and mammalian pigment granules (Dell'Angelica et al, 1997;Simpson et al, 1997;Kantheti et al, 1998). Conflicting results have been obtained as to whether the AP-3 complex is associated with clathrin.…”
Section: Introductionmentioning
confidence: 99%